1992
DOI: 10.1096/fasebj.6.10.1634045
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant congenic strains for analysis of multigenic traits: genetic composition

Abstract: The genetic control of susceptibility to many common diseases, including cancer, is multigenic both in humans and in animals. This genetic complexity has presented a major obstacle in mapping the relevant genes. As a consequence, most geneticists and molecular biologists presently focus on "single gene" diseases. To make the multigenic diseases accessible to genetic and molecular analysis, we developed a novel genetic tool, the recombinant congenic strains (RCS) in the mouse (4). The RC strains are produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…Theoretical considerations predict that $95% of the genome of the donor strain can be transferred and distributed within a series of 20 RCSs (Demant and Hart 1986;Moen et al 1997). Five sets of such RCSs have been produced between pairs of laboratory inbred strains (Groot et al 1992;Martin et al 1992b;Fortin et al 2001b) and the results have fulfilled the theoretical expectations . Since each RCS carries only a small fraction of the donor genome, multiple genes controlling a trait are likely to be isolated in different strains (Demant and Hart 1986;Moen et al 1991).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Theoretical considerations predict that $95% of the genome of the donor strain can be transferred and distributed within a series of 20 RCSs (Demant and Hart 1986;Moen et al 1997). Five sets of such RCSs have been produced between pairs of laboratory inbred strains (Groot et al 1992;Martin et al 1992b;Fortin et al 2001b) and the results have fulfilled the theoretical expectations . Since each RCS carries only a small fraction of the donor genome, multiple genes controlling a trait are likely to be isolated in different strains (Demant and Hart 1986;Moen et al 1991).…”
mentioning
confidence: 70%
“…We observed that in 87% of cases, strains segregating for the two alleles at a particular locus in the first series of genotyping (average F ¼ 8.7) had fixed the B6 allele in the second series (average F ¼ 24.6). No such genomewide selection has been observed in recombinant inbred or recombinant congenic strains established from laboratory strains, which showed the expected proportion from the two parental strains (Groot et al 1992;Stassen et al 1996). The final genetic makeup of IRCSs and ICSs suggests that it is hardly feasible to introduce .4-5% of the M. spretus genome in a B6 background, because of the large number of interchromosomal epistatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we studied TXNIP-deficient HcB-19 mice. HcB-19 mice are an inbred congenic C3H mouse strain (33,34) that harbors a spontaneous inactivating nonsense mutation in exon 2 at codon 97, resulting in dramatically reduced TXNIP mRNA and protein levels (29). Glucose induces TXNIP expression and apoptosis in primary islets.…”
Section: Resultsmentioning
confidence: 99%
“…18 In several diseases, the recombinant congenic (RC) strains of mice have proven to be a powerful tool to provide the mapping of genes controlling complex traits. 17,[19][20][21][22][23][24][25][26][27] A series of RC strains comprises approximately 20 homozygous strains, each of which contains on average 87.5% genes of a common background strain and 12.5% of a common donor strain. 26,28 In this way, the RC system transforms a multigenic difference into a set of mono-or oligogenic differences and hence offers higher resolution power in mapping the quantitative trait loci and detecting their mutual interactions than the standard genetic methods.…”
Section: Polymorphisms Of Both Adam33 and Spink5mentioning
confidence: 99%